Econometrics - Hansen, Bruce E. (University of Wisconsin, 2012)
Econometrics is the study of estimation and inference for economic models using economic data. Econometric theory concerns the study and development of tools and methods for applied econometric applications. Applied econometrics concerns the application of these tools to economic data.